An integrative approach to assessing effects of a short-term Western diet on gene expression in rat liver - Welles, Jaclyn E.; Lacko, Holly; Kawasawa, Yuka Imamura; Dennis, Michael D.; Jefferson, Leonard S.; Kimball, Scot R. (Frontiers in Endocrinology, 2022)
Consumption of a diet rich in saturated fatty acids and carbohydrates contributes to the accumulation of fat in the liver and development of non-alcoholic steatohepatitis (NASH). Herein we investigated the hypothesis that short-term consumption of a high fat/sucrose Western diet (WD) alters the genomic and translatomic profile of the liver in association with changes in signaling through the protein kinase mTORC1, and that such alterations contribute to development of NAFLD. The results identify a plethora of mRNAs that exhibit altered expression and/or translation in the liver of rats consuming a WD compared to a CD. In particular, consumption of a WD altered the abundance and ribosome association of mRNAs involved in lipid and fatty acid metabolism, as well as those involved in glucose metabolism and insulin signaling. Hepatic mTORC1 signaling was enhanced when rats were fasted overnight and then refed in the morning; however, this effect was blunted in rats fed a WD as compared to a CD. Despite similar plasma insulin concentrations, fatty acid content was elevated in the liver of rats fed a WD as compared to a CD. We found that feeding had a significant positive effect on ribosome occupancy of 49 mRNAs associated with hepatic steatosis (e.g., LIPE, LPL), but this effect was blunted in the liver of rats fed a WD. In many cases, changes in ribosome association were independent of alterations in mRNA abundance, suggesting a critical role for diet-induced changes in mRNA translation in the expression of proteins encoded by those mRNAs. Overall, the findings demonstrate that short-term consumption of a WD impacts hepatic gene expression by altering the abundance of many mRNAs, but also causes wide-spread variation in mRNA translation that potentially contribute to development of hepatic steatosis.